South American geoarchaeology: Contributions after the 21st National Chilean Archaeology Conference. Issue 1 (20th December 2021) - Sitzia, Luca; Ugalde, Paula C.; Holliday, Vance T.
Abstract: In this special issue, articles include research from Argentina, Brazil, Chile, Colombia, and Uruguay, plus a special paper from the United States of America. Several of the articles are from Chilean scientists and/or focus on Chilean geoarchaeology and are intended to reflect the spirit of the symposium carried out during the Congreso Nacional de Arqueología Chilena 2018 (National Chilean Archaeology Conference). The topics, techniques, and research questions of the articles in this special issue are varied, but we have recognized four main themes that are common and encompass all the contributions: (1) Late Pleistocene–Early Holocene human settlement or migration; (2) pre‐Hispanic soil use and conservation; (3) monumental landscape modification—shell middens and mounds; and (4) bioarchaeology and mobility.